A method for determining the content of pre-crosslinked polymer in rock core
By ultrasonic crushing and aluminum nitrate reaction on the core sample, combined with polyacrylamide liquid chromatography analysis, the problem of detection of B-PPG content in the core was solved, accurate quantity detection was achieved, and technical gaps were filled.
Patent Information
- Application Number
- CN202011213261.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-11-03
AI Technical Summary
The prior art is difficult to accurately detect the content of pre-crosslinked polymer B-PPG or PPG in cores, especially in the case where it coexists with linear polyacrylamide (PAM).
The core sample was dissolved in water and then crushed ultrasonicly, the branched polymer chains were sheared, and aluminum nitrate was added for reaction, followed by polyacrylamide liquid chromatography analysis, and the content of the pre-crosslinked polymer was calculated according to the standard curve.
Quantitative detection of pre-crosslinked polymer B-PPG in the core is realized, filling the gap in the existing technology, and the detection method is fast, simple, reliable, accurate and highly sensitive.
Smart Images

Figure CN114441660B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oilfield analytical chemistry, and in particular relates to a method for determining the content of pre-crosslinked polymers in a core. Background Art
[0002] Viscoelastic particle flooding agent (B-PPG) has a partially cross-linked structure and a partially branched molecular structure. It has the dual advantages of linear polyacrylamide and cross-linked polyacrylamide in terms of performance. It is dispersed in water to form a heterogeneous polymer suspension. It can achieve the effect of adjusting and flooding in heterogeneous reservoirs. The heterogeneous composite flooding method with it as the main agent has achieved good field application results in the Ng3 pilot test in the first area of the Gudao Oilfield in Shengli Oilfield, and has great application potential. In order to further carry out the research on the B-PPG flooding mechanism and understand the migration of B-PPG in the formation, it is necessary to detect the content of B-PPG in the cores produced from different formations. However, at present, the detection of B-PPG in cores at home and abroad is still blank.
[0003] Chinese invention patent CN102914511B discloses a quantitative detection method for polyacrylamide in a composite / mixture, which utilizes the principle that NH in the amide functional group in polyacrylamide undergoes a substitution reaction with sodium hypochlorite under acidic conditions, and uses a spectrophotometer to detect the concentration change of sodium hypochlorite before and after the reaction under alkaline conditions, thereby indirectly quantitatively detecting polyacrylamide. This method can be used for quantitative detection of polyacrylamide in a composite / mixture, and can also be used to detect the content of polyacrylamide in a swollen state in water by adding non-adsorbent particles to promote flocculation.
[0004] Chinese patent application CN111595963A discloses a method for determining the hydrolysis degree of partially hydrolyzed polyacrylamide in a chemical flooding production fluid of an oil and gas field. The method comprises the following steps: S1, preparing hydrolysis degree standards of partially hydrolyzed polyacrylamide with different hydrolysis degrees and calibrating the hydrolysis degree; S2, preparing a series of partially hydrolyzed polyacrylamide standard solutions; S3, drawing a relationship curve between the chromatographic peak area or peak height of the partially hydrolyzed polyacrylamide standard solution and the partially hydrolyzed polyacrylamide concentration according to the measured data; S5, measuring the sample to be measured by the same method as that for measuring the partially hydrolyzed polyacrylamide standard solution, and calculating the slope kx of the straight line; and S6, finding the corresponding hydrolysis degree on the curve according to the kx value of the sample to be measured or calculating it using a relationship.
[0005] Chinese patent application CN101825579A discloses a method for determining the concentration of a polyacrylamide solution. A series of colloid titration values are measured by colloid titration method, a standard curve of colloid titration value V and corresponding concentration C is established, and a calculation formula is fitted; for a partially hydrolyzed polyacrylamide solution of a concentration to be measured, an excess of a standard positive ion reagent PD is first added, and then the excess positive ion reagent is titrated with a standard solution of a negative ion reagent PVSK, and TBO is used as an indicator to measure the colloid titration value required at the titration end point; three groups of parallel experiments are performed on the sample to be tested, and the average value is taken, and the average value is substituted into the fitted calculation formula to calculate the concentration of the polyacrylamide.
[0006] Chinese invention patent CN102564899B discloses a method for determining the degree of intermolecular association contribution in a hydrophobically associating polyacrylamide solution, the method comprising the following steps:
[0007] 1) dissolving associative polyacrylamide in deionized water to obtain a polymer mother solution;
[0008] 2) dissolving β-cyclodextrin or a β-cyclodextrin derivative in deionized water to obtain a β-cyclodextrin mother solution;
[0009] 3) mixing the polymer mother solution obtained in step 1), the β-cyclodextrin mother solution obtained in step 2) and deionized water to obtain an associative polyacrylamide solution to be tested;
[0010] 4) The zero shear viscosity of the associative polyacrylamide solution to be tested obtained in step 3) is measured in accordance with the following method when [CD] / [H]=0 and 4: the associative polyacrylamide solution to be tested obtained in step 3) is sheared and then allowed to stand to obtain a stress sweep viscosity curve, and then the Carreau-Yasuda model is used for calculation to obtain the zero shear viscosity y0 (associated state) and y0 (non-associated state) of the associative polyacrylamide solution to be tested;
[0011] The Carreau-Yasuda model equation is shown in Formula I:
[0012] y=(y 0-y inf)*(1+(λ*x)a)n-1a+y inf (Formula I)
[0013] In the formula I, y is the input viscosity, in Pa.s; x is the input shear rate, in S-1; y 0 is the zero shear viscosity, in Pa.s; y inf is the limiting shear viscosity, in Pa.s; λ is the characteristic relaxation time, in s; a is the Carreau constant; n is the Carreau index;
[0014] The [CD] / [H] are the molar ratios of β-cyclodextrin or β-cyclodextrin derivatives in the β-cyclodextrin mother solution obtained in step 2) to the associative polyacrylamide in the polymer mother solution obtained in step 1);
[0015] 5) Substituting the zero shear viscosity y 0 (associated state) and y 0 (non-associated state) of the associative polyacrylamide solution to be tested obtained in step 4) into formula II for calculation to obtain the degree of association contribution between the associative polyacrylamide molecules to be tested;
[0016] From the above analysis, it can be seen that the current existing technologies mostly involve methods for determining the hydrolysis degree, concentration and contribution of intermolecular association of polyacrylamide, while there are no relevant reports on the determination of the network structure content in polyacrylamide solution.
[0017] In the oil displacement process, since PAM and B-PPG or PPG are used in combination, these two polymers exist in two states on the core after sufficient shear adsorption of the core, namely linear polyacrylamide and network structure polyacrylamide. There is still no effective solution for accurately and quantitatively detecting the content of B-PPG or PPG in the core samples in this state. Therefore, it is an indispensable research work to establish a method for detecting the content of pre-crosslinked polymers (B-PPG or PPG) in cores containing linear polyacrylamide (PAM). Summary of the invention
[0018] The main purpose of the present invention is to provide a method for determining the content of pre-crosslinked polymer in a core. The method of the present invention can accurately detect the content of pre-crosslinked polymer (B-PPG or PPG) in a core that may contain linear polyacrylamide (PAM), thus filling the existing gap.
[0019] To achieve the above object, the present invention adopts the following technical solutions:
[0020] The present invention provides a method for determining the content of a pre-crosslinked polymer in a core, the method comprising:
[0021] Preparation of standard curve;
[0022] Weigh the core sample to be tested, dissolve it in water, and perform ultrasonic crushing;
[0023] Add aluminum nitrate to the supernatant after ultrasonic disruption, mix well and let the solution stand to allow the reaction to complete;
[0024] The solution after the reaction was analyzed by polyacrylamide liquid chromatography, and the content of the pre-crosslinked polymer in the core sample was calculated according to the standard curve.
[0025] Furthermore, the preparation method of the standard curve includes: (1) adding different amounts of mixed powder of pre-crosslinked polymer and PAM into multiple 10 g simulated cores to prepare standard added core samples;
[0026] (2) adding 20 mL of water to the above-mentioned standard spiked core samples respectively, and performing ultrasonic crushing to transfer all the pre-crosslinked polymer and PAM into the aqueous solution;
[0027] (3) After standing and stratifying, take 1 mL of the supernatant and add aluminum nitrate, mix well, and stand to allow the reaction to complete;
[0028] (4) The post-reaction solution was subjected to polyacrylamide liquid chromatography analysis, and a standard curve was drawn with the polyacrylamide chromatographic peak area as the ordinate and the pre-crosslinked polymer content (mg / g) in the core as the ordinate.
[0029] Furthermore, the ultrasonic crushing conditions are: 15000-18000W ultrasound for 4-5min.
[0030] Due to the presence of branched polymer chains in the outer layer, PPG or B-PPG gel particles will also undergo slow and reversible complexation with aluminum nitrate when aluminum nitrate is added to the solution. Therefore, it is difficult to quantify PPG or B-PPG in the core sample where PAM, PPG or B-PPG coexist by detecting polyacrylamide by liquid chromatography. The method of the present invention dissolves the core sample in water and then performs ultrasonic crushing. Under the ultrasonic crushing conditions described above, on the one hand, the branched polymer chains in the outer layer of the gel particles are sheared off and then complexed with aluminum nitrate, and on the other hand, the gel particles are broken into very small network structures. The cross-linking points of polyacrylamide are not complexed with aluminum nitrate. Therefore, the solution after ultrasonic crushing can directly use aluminum nitrate to eliminate the interference of linear polymers. In addition, it can also avoid the large volume of the complex formed by long-chain polymers and aluminum nitrate, forming a precipitate visible to the naked eye, which will wrap the gel particles and affect the accurate detection of PPG or B-PPG.
[0031] Furthermore, the aluminum nitrate used is Al(NO3)3·9H2O.
[0032] Furthermore, the amount of Al(NO3)3·9H2O added is 0.10-0.15g. The amount of aluminum nitrate added has a great influence on the drawing of the standard curve. This is because the addition of aluminum nitrate is mainly to completely complex the linear polymer. If the amount added is too little, the linear polymer complex is incomplete, resulting in a larger B-PPG test result; if the amount of aluminum nitrate added is too large, the excess aluminum nitrate, as a strong electrolyte, will destroy the previously generated complex, thereby causing the linear polymer to be partially released, which will also cause the B-PPG test result to be larger. After a large number of experiments and analyses, it was found that adding 0.1-0.15g of aluminum nitrate to 1mL of the above supernatant can not only completely complex the linear polymer, but also will not cause the complex formed due to excessive electrolyte concentration to be released.
[0033] Furthermore, the liquid chromatography conditions of polyacrylamide are as follows: chromatographic column: polyacrylamide-specific chromatographic column ID 4.6 mm × 150 mm;
[0034] Mobile phase: 250 mM NaH2PO4;
[0035] Flow rate: 1 mL / min;
[0036] Detector: UV;
[0037] Detection wavelength: 200nm.
[0038] Furthermore, the polyacrylamide chromatographic peak is the chromatographic peak at a retention time of 1.0 min.
[0039] Further, aluminum nitrate was added, mixed evenly, and allowed to stand at 4° C. for 8-12 h.
[0040] Furthermore, the cross-linked polymer is a viscoelastic surfactant B-PPG or a viscoelastic surfactant PPG.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The method of the present invention can realize the quantitative detection of the pre-crosslinked polymer B-PPG in the core, filling the gap in the prior art.
[0043] The detection method of the present invention has the advantages of fast analysis speed, simple operation, safety and reliability, high accuracy, good repeatability and high sensitivity. When the content of B-PPG in the core is between 0.01 mg / g and 0.60 mg / g, it has a good linear relationship, and its linear correlation coefficient is 0.999. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0045] Figure 1 It is a polyacrylamide liquid chromatography;
[0046] Figure 2 This is a standard curve of B-PPG content in the core described in Example 1 of the present invention;
[0047] Figure 3 This is a standard curve of B-PPG content in the core described in Example 2 of the present invention;
[0048] Figure 4 This is a standard curve of B-PPG content in the core described in Example 3 of the present invention. DETAILED DESCRIPTION
[0049] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0050] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.
[0051] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0052] The following examples use core samples containing the viscoelastic particle oil displacement agent B-PPG as research objects, and the method described in the present invention is also applicable to the determination of the PPG content of the viscoelastic particle oil displacement agent.
[0053] Example 1
[0054] A method for determining the content of pre-crosslinked polymer in a core:
[0055] 1. Preparation of standard curve:
[0056] (1) 5 portions of 10 g simulated cores were added with 0.2 mg B-PPG + 0.2 mg PAM, 0.4 mg B-PPG + 0.4 mg PAM, 1.0 mg B-PPG + 1.0 mg PAM, 2.0 mg B-PPG + 2.0 mg PAM, and 4.0 mg B-PPG + 4.0 mg PAM, respectively, to prepare standard added core samples;
[0057] (2) Add 20 mL of water to each of the five standard spiked core samples, and use an ultrasonic crusher at 18,000 W for 4 min to transfer all of the B-PPG and PAM into the aqueous solution;
[0058] (3) After standing for stratification, take 1 mL of the supernatant and add 0.12 g of Al(NO3)3·9H2O. Shake evenly to dissolve the aluminum salt completely. Then seal the solution and place it in a refrigerator at 4°C for 8 h to allow the reaction to complete.
[0059] (4) The above solution was tested by liquid chromatography detection method of polyacrylamide, and a standard curve was drawn with the peak area of polyacrylamide chromatography as the ordinate and the B-PPG content (mg / g) in the core as the ordinate (e.g. Figure 2 As shown), the linear regression equation is Y = 4759.7X-3.0746, R 2 =0.9999. This indicates that when the B-PPG content is in the range of 0.02 mg / g to 0.4 mg / L, the polyacrylamide peak area and the B-PPG content have a good linear relationship.
[0060] 2. Testing of actual samples
[0061] (1) Weigh 3 portions of 10 g of actual oil field cores, add 20 mL of water to each portion, and use an ultrasonic crusher at 18000 W for 4 min to transfer all B-PPG and PAM into the aqueous solution;
[0062] (2) After standing and stratifying, take 1 mL of the supernatant and add 0.12 g of Al(NO3)3·9H2O. Shake evenly to dissolve the aluminum salt completely. Then seal the solution and place it in a refrigerator at 4°C for 8 h to allow the reaction to complete.
[0063] (3) The above solution was tested by liquid chromatography detection method of polyacrylamide, and the obtained chromatographic peak area was substituted into the above standard curve. The B-PPG content obtained from the three samples was averaged to obtain the B-PPG content of 0.13 mg / g in the actual core of the oil field.
[0064] Example 2
[0065] A method for determining the content of pre-crosslinked polymer in a core:
[0066] 1. Preparation of standard curve:
[0067] (1) Six portions of 10 g simulated cores were added with 0.2 mg B-PPG + 0.2 mg PAM, 0.4 mg B-PPG + 0.4 mg PAM, 1.0 mg B-PPG + 1.0 mg PAM, 2.0 mg B-PPG + 2.0 mg PAM, 4.0 mg B-PPG + 4.0 mg PAM, and 6.0 mg B-PPG + 6.0 mg PAM to prepare standard added core samples;
[0068] (2) 20 mL of water was added to each of the six standard spiked core samples, and ultrasonicated for 5 min at 17,000 W using an ultrasonic crusher to transfer all of the B-PPG and PAM into the aqueous solution;
[0069] (3) After standing for stratification, take 1 mL of the supernatant and add 0.15 g of Al(NO3)3·9H2O. Shake evenly to dissolve the aluminum salt completely. Then seal the solution and place it in a refrigerator at 4°C for 12 h to allow the reaction to complete.
[0070] (4) The above solution was tested by liquid chromatography detection method of polyacrylamide, and a standard curve was drawn with the peak area of polyacrylamide chromatography as the ordinate and the B-PPG content (mg / g) in the core as the ordinate (e.g. Figure 3 As shown), the linear regression equation is Y = 4706.4X-8.4439, R 2 =0.9999. This indicates that when the B-PPG content is in the range of 0.02 mg / g to 0.60 mg / L, the polyacrylamide peak area and the B-PPG content have a good linear relationship.
[0071] 2. Testing of actual samples
[0072] (1) Weigh 3 portions of 10 g of actual oil field cores, add 20 mL of water to each portion, and use an ultrasonic crusher at 17000 W for 5 min to transfer all B-PPG and PAM into the aqueous solution;
[0073] (2) After standing and stratifying, take 1 mL of the supernatant and add 0.15 g of Al(NO3)3·9H2O. Shake evenly to dissolve the aluminum salt completely. Then seal the solution and place it in a refrigerator at 4°C for 12 h to allow the reaction to complete.
[0074] (3) The above solution was tested by liquid chromatography detection method of polyacrylamide, and the obtained chromatographic peak area was substituted into the above standard curve. The B-PPG content obtained from the three samples was averaged to obtain the B-PPG content in the actual core of the oil field, which was 0.36 mg / g.
[0075] Example 3
[0076] A method for determining the content of pre-crosslinked polymer in a core:
[0077] 1. Preparation of standard curve:
[0078] (1) 5 portions of 10 g simulated cores were added with 0.1 mg B-PPG + 0.1 mg PAM, 0.2 mg B-PPG + 0.2 mg PAM, 0.4 mg B-PPG + 0.4 mg PAM, 1.0 mg B-PPG + 1.0 mg PAM, and 2.0 mg B-PPG + 2.0 mg PAM to prepare standard added core samples;
[0079] (2) Add 20 mL of water to each of the five standard spiked core samples, and use an ultrasonic crusher at 15,000 W for 4 min to transfer all of the B-PPG and PAM into the aqueous solution;
[0080] (3) After standing for stratification, take 1 mL of the supernatant and add 0.10 g of Al(NO3)3·9H2O. Shake evenly to dissolve the aluminum salt completely. Then seal the solution and place it in a refrigerator at 4°C for 10 h to allow the reaction to complete.
[0081] (4) The above solution was tested by liquid chromatography detection method of polyacrylamide, and a standard curve was drawn with the peak area of polyacrylamide chromatography as the ordinate and the B-PPG content (mg / g) in the core as the ordinate (e.g. Figure 4 As shown), the linear regression equation is Y = 4583.3X-2.1667, R 2 =0.9992. This indicates that when the B-PPG content is in the range of 0.01 mg / g to 0.20 mg / L, the polyacrylamide peak area and the B-PPG content have a good linear relationship.
[0082] 2. Testing of actual samples
[0083] (1) Weigh 3 portions of 10 g of actual oil field cores, add 20 mL of water to each portion, and use an ultrasonic crusher at 15,000 W for 4 min to transfer all B-PPG and PAM into the aqueous solution;
[0084] (2) After standing and stratifying, take 1 mL of the supernatant and add 0.10 g of Al(NO3)3·9H2O. Shake evenly to dissolve the aluminum salt completely. Then seal the solution and place it in a refrigerator at 4°C for 10 h to allow the reaction to complete.
[0085] The above solution was detected by liquid chromatography detection method of polyacrylamide, the obtained chromatographic peak area was substituted into the above standard curve, and the B-PPG content obtained from three samples was averaged to obtain the B-PPG content of 0.05 mg / g in the actual core of the oil field.
[0086] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for determining the content of pre-crosslinked polymer in a core, characterized in that: The method comprises: Preparation of standard curve; Weigh the core sample to be tested, dissolve it in water, and perform ultrasonic crushing; Add aluminum nitrate to the supernatant after ultrasonic disruption, mix well and let the solution stand to allow the reaction to complete; The solution after the reaction is analyzed by polyacrylamide liquid chromatography, and the content of the pre-crosslinked polymer in the core sample is calculated according to the standard curve; The method for preparing the standard curve comprises: (1) Multiple 10 g simulated cores were doped with different amounts of pre-crosslinked polymer and PAM mixed powder to prepare standard added core samples; (2) adding 20 mL of water to the above-mentioned standard spiked core samples respectively, and performing ultrasonic crushing to transfer all the pre-crosslinked polymer and PAM into the aqueous solution; (3) After standing and stratifying, take 1 mL of the supernatant and add aluminum nitrate, mix well, and stand to allow the reaction to complete; (4) The solution after the reaction was analyzed by polyacrylamide liquid chromatography, and a standard curve was drawn with the polyacrylamide chromatographic peak area as the ordinate and the B-PPG content (mg / g) in the core as the abscissa; The ultrasonic crushing conditions are: 15000-18000W ultrasound for 4-5min; The aluminum nitrate is Al(NO3)3·9H2O; the amount of Al(NO3)3·9H2O added is 0.10-0.15g; The liquid chromatography conditions of the polyacrylamide are as follows: chromatographic column: polyacrylamide special chromatographic column ID 4.6mm×150mm; mobile phase: 250mM NaH2PO4; flow rate: 1mL / min; detector: UV; detection wavelength: 200nm; polyacrylamide chromatographic peak is the chromatographic peak at retention time 1.0min; aluminum nitrate is added and mixed evenly, and then allowed to stand at 4°C for 8-12h; The cross-linked polymer is a viscoelastic surfactant B-PPG or a viscoelastic surfactant PPG.
Citation Information
Patent Citations
Method for measuring concentration of polyacrylamide solution
CN101825579A
Method for determining intermolecular association degree of contribution in hydrophobically-associating type polyacrylamide solution
CN102564899B
Quantitative detecting method for polyacrylamide in composite / mixture
CN102914511B
Method for determining hydrolysis degree of partially hydrolyzed polyacrylamide in oil and gas field chemical flooding output liquid
CN111595963A
Sample pretreatment method for detecting PPG in a PAM-containing oilfield extraction liquid
CN107367563A